GAMBARAN TINGKAT PENGETAHUAN SWAMEDIKASI PENGGUNAAN OBAT DISMENOREA PADA KELAS 12 SMK NEGERI 1 BASO - Mulyani, Dwi; Haryani, Cindy; Febriyoldini Elwan, Shaula (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2025)
Dysmenorrhea is also called menstrual cramps or menstrual pain. Primary dysmenorrhea is a mild disease that can be cured with self-medication. Self-medication is the behavior of taking one's own medication based on a diagnosis of the symptoms one is suffering from. Self-medication is also part of